Standardization in Digital Teaching and Learning in Higher Education: Indonesia Evidence - Kristanto, Andi; Aisyah, Siti; Febrianti, Farida; Dewi, Utari; Pujiriyanto; Hidayati, Abna; Budi, UL; Susarno, Lamijan Hadi (Universitas Pendidikan Ganesha, 2024)
This research is motivated by the existence of new learning trends in the form of digital learning such as blended learning, online learning, MOOC, e-learning and various new learning trends that emerged in the era of the industrial revolution, but more effective digital learning standards have not yet been established. So this research aims to produce digital learning standards that are appropriate to the Indonesian context with diverse demographic and geographical conditions so that it is hoped that they can become guidelines for implementing digital learning in Indonesia, especially at the higher education level. This article specifically carries out the needs analysis process. This type of research is R & D using the 4D development method (define, design, development and dissemination) with research subjects of 50 students taken from 3 universities. The instruments used were questionnaires, observation and interview guidelines and were processed using a mixed method (a mix of qualitative and quantitative). Based on the results of the needs analysis, it is known that technological developments have been utilized by various levels of education to facilitate learning and overcome learning gaps evenly. There are also many case studies that prove that the presence of technology in learning makes learning much more optimal. However, there are no specific standards set to make the digital learning process more effective. Therefore, innovation is needed to produce digital learning standards.